PENGARUH KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERATING - ., Surono (AKTUAL, 2014)
The purpose of this study is to investigate the influence of leadership and organization commitment to teachers performance with job satisfaction as a moderating at The Government Vocational High School 4 at Klaten. The Hypothesis which have been formulated in this research are: there is influence of leadership and organization commitment to teachers performance with job satisfaction as a moderating at The Government Vocational High School 4 at Klaten. The research is a survey to the teachers of The Government Vocational High School 4 at Klaten. Data of this research are primary. Data have been collected with questionnaires processed with assumption of regression test, the moderated regression analysis, t test, F test and test of R2 The t test result shows that leadership and organization commitment have an influence to teachers performance with job satisfaction as a moderating partially. The F tes shows that the leadership and organization commitment have an influence to teachers performance with job satisfaction as a moderating at The Government Vocational High School 4 at Klaten simultaneously. From the moderated regression analysis shows that job satisfaction canât be a moderating variable to leadership toward performance but for influence of organization commitment toward performance can be moderated job satisfaction. From test of R2 show the independent variable can explain productivity about 84,2 %and 15,8% can be explained another variable like that job environment, job ability. Keyword: leadership, organization commitment, performance, job satisfaction